Impact of the covid-19 pandemic on physical education: Investigating basic motor skills, physical activity, fitness, and academic achievement - Pratama, Budiman Agung; Hanief, Yulingga Nanda; Prasetiyo, Reo; Shandy, Dwi Kurnia; Muharram, Nur Ahmad (UIR Press, 2023)
The physical education learning process due to the covid-19 pandemic which resulted in students doing distance learning, limiting physical activity, and having to be physical distanced, became a challenge for students to be able to complete academic achievements in physical education. The purpose of the study of impact covid-19 on basic motor skills, physical activity, fitness, and academic achievement in Physical Education in 9-10-years-old School Children. Materials and methods this study were a correlation study, the object of as many as 80 elementary school students in the Lamongan district aged 9-10 years, who had a body mass index of 19-25 kg/m, normal blood pressure, and normal heart rate voluntarily became a study sample. Data collection for basic motor skills used TGMD-2, Physical activity used PAQ-C, and Fitness used the Indonesian Academic Achievement in Physical Education, Fitness Test used student report cards taken after one semester. The analysis sample used correlation with a significant rate of 0.05%. The result correlation showed that BMS and F were significantly correlated to AA but not correlated to PA (p < 0.000) whereas BMS was significantly correlated to PA and F using (p < 0.000). Conclusions of the study show that the impact of covid-19 affects learning achievement in Physical Education in 9-10-years-old School Children, variables that affect learning outcomes Physical Education are basic motor skills and fitness, while variables of physical activity and fitness directly affect the basic motor skills of students, then the learning outcomes of physical education in school programs are indirectly influenced by physical activity. Future research should conduct an investigation into the variables that are consistently associated with academic success in physical education among young children. This will provide a comprehensive understanding of the topic.